Strategic Mentoring in School Development Planning for Special Needs Schools: A Model for Enhancing Educational Quality in Manggarai Regency - Fransiskus Sawan; Kristianus Viktor Pantaleon; Marselinus Robe (Asosiasi Profesi Multimedia Indonesia, 2025)
Background: The development of a School Strategic Plan (SSP), based on internal and external environmental analysis and aligned with the National Education Standards, is a crucial component for improving the quality of education, including in Special Needs Schools (SNS). However, many principals and teachers in SNSs have a limited understanding of strategic planning concepts. They also lack the skills to use analytical tools such as SWOT and to apply National Education Standards instruments in school planning.Aims: This community service activity aimed to enhance the competence of principals and teachers in four SNSs in Manggarai Regency through intensive and structured mentoring.Methods: The methods used included mapping surveys, material presentations, guided document revisions, and SSP evaluations. The instruments employed were pretest-posttest questionnaires on SSP, which assessed six key aspects of planning competence, existing SSP documents from the schools, and National Education Standards mapping questionnaires used to evaluate the initial implementation of quality culture. A T-test was applied to analyze differences in pretest and posttest scores, while the SSP document analysis was conducted qualitatively.Results: The mentoring results showed a significant improvement in participants’ competence in developing SSPs, as indicated by the increase in pretest-posttest questionnaire scores. A T-test confirmed a statistically significant difference between the pretest and posttest results (T = -62.63; P < 0.05).Conclusion: This mentoring model is both replicable and sustainable for improving the quality of educational management in Special Needs Schools and strengthening school accreditation.